Laser spectroscopic technique for direct identification of a single virus I: FASTER CARS - Deckert, Volker; Deckert-Gaudig, Tanja; Cialla-May, Dana; Popp, Jürgen; Zell, Roland; Deinhard-Emmer, Stefanie; Sokolov, Alexei V.; Yi, Zhenhuan; Scully, Marlan O. (Proceedings of the National Academy of Sciences - PNAS, 2020)
From the famous 1918 H1N1 influenza to the present COVID-19 pandemic, the need for improved viral detection techniques is all too apparent. The aim of the present paper is to show that identification of individual virus particles in clinical sample materials quickly and reliably is near at hand. First of all, our team has developed techniques for identification of virions based on a modular atomic force microscopy (AFM). Furthermore, femtosecond adaptive spectroscopic techniques with enhanced resolution via coherent anti-Stokes Raman scattering (FASTER CARS) using tip-enhanced techniques markedly improves the sensitivity [M. O. Scully, et al., Proc. Natl. Acad. Sci. U.S.A. 99, 10994–11001 (2002)].